AUDIT SISTEM INFORMASI PADA PERUSAHAAN DAGANG ANEKA GEMILANG BANDAR LAMPUNG MENGGUNAKAN FRAMEWORK COBIT 4.1 - amnah, Amnah (IIB Darmajaya, 2012)
Aneka Gemilang Trade Enterprises is a trading company that engaged in the trade field, particularly in learning tool needs from primary school to college. Now days, there are many the same type of business, it is certainty tighten the competition, as well as in the product quality side until the quality of services to customers. To measure the quality and service which are provided by the Aneka Gemilang Trade Enterprises can be focused and balanced with the company business objectives, it is needed to determine the alignment level of TI objectives with company objectives. In order to achieve the alignment between TI objectives and company objectives, it is required a measurement of balance level between company objectives with TI objectives using COBIT 4.1. By this audit decision, it is expected there is a significant progress toward the company. The optimum of service and provide of qualified goods are the activities that must be priority to strengthen the available business partner and try to add the business partner in the future, therefore Aneka Gemilang Trade Enterprise be able to open the branches in other potential district.Key Words: Maturity Level, Expected, Trade Enterprise, COBIT